Dampak Penggunaan Anotasi Penamaan yang Berbeda pada Kinerja NER - Saputra, I Made Widi Arsa Ari; Supriana, I Wayan (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 4 (2023): JNATIA Vol. 1, No. 4, Agustus 2023DO - 10.24843/JNATIA.2023.v01.i04.p16, 2023)
In developing the NER model, naming annotations are used as an important part of the training process.  The  impact  of  using  different  naming  annotations  on  NER  performance  has  been  a concern in the research community. So,the writer wants to once again, test the impact of using different  naming  annotations  using  the  spaCy  library  on  English  documents.  Using  2  naming schemes namely BIO and IOBES, using the spaCy model to get 0.96 accuracy for BIO and 0.95 for IOBES.